Ecological security evaluation and spatial–temporal evolution characteristics of natural resources Based on wind-driven optimization algorithm - Ke, X.; Shi, W.; Yang, C.; Guo, H.; Mougharbel, A. (International journal of environmental science and technology (Tehran), 2022)
Urban natural resources comprise a complex system of water, land, forest, and air. They are the essential elements of sustainable economic and social development. However, few studies have been conducted on the dynamic relationship between multi-resource ecosystem and natural resource ecological security. The present study aims to systematically examine the impact of water, land, forest, and air resource ecosystem on natural resource ecological security. First, this study establishes the ecological security evaluation system of natural resources based on the driving force-pressure-state-response model. Second, the study takes the Guangdong–Hong Kong–Macao Greater Bay Area as an example, and uses the wind-driven optimization algorithm to optimize the projection pursuit model to calculate the value of ecological security level. Then, it analyzes the spatial layout of regional natural resources ecological security, and discusses the influence mechanism of water, land, forest, and air resource subsystems on ecological security for natural resources. The study shows that the ecological security level of natural resources in nine cities in the Guangdong–Hong Kong–Macao Greater Bay Area increased as a whole from 2013 to 2018. However, the ecological security level in the central region of the Guangdong–Hong Kong–Macao Greater Bay Area is low, which is directly related to the severe environmental pollution of its water and air resources. The conclusions of this study are consistent with the reality and have high reliability. Therefore, this study can enrich the evaluation methods of ecological security and provide scientific guidance for improving urban natural resources and environment.